2014
DOI: 10.5194/gmd-7-2639-2014
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of the CLaMS Lagrangian transport core into the chemistry climate model EMAC 2.40.1: application on age of air and transport of long-lived trace species

Abstract: Abstract. Lagrangian transport schemes have proven to be useful tools for modelling stratospheric trace gas transport since they are less diffusive than classical Eulerian schemes and therefore especially well suited for maintaining steep tracer gradients. Here, we present the implementation of the full-Lagrangian transport core of the Chemical Lagrangian Model of the Stratosphere (CLaMS) into the ECHAM/MESSy Atmospheric Chemistry model (EMAC). We performed a 10-year time-slice simulation to evaluate the coupl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 48 publications
7
59
0
Order By: Relevance
“…In contrast EMAC-RC1SD uses the flux-form semi-Lagrangian transport scheme, where (numerical) diffusion is more pronounced in regions of strong barriers (e.g., at the arctic and antarctic polar vortex), so unresolved diffusion is higher than in CLaMS there. This is consistent with Hoppe et al (2014), who found in free-running simulations with the coupled model system EMAC-CLaMS, that transport barriers (polar vortex and tropical pipe) are stronger, if using the CLaMS tracer transport scheme compared to FFSL transport scheme. The stronger transport barrier in CLaMS can be also seen in Fig.…”
Section: Calculation Of Aging By Mixing On Resolved and Unresolved Scsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast EMAC-RC1SD uses the flux-form semi-Lagrangian transport scheme, where (numerical) diffusion is more pronounced in regions of strong barriers (e.g., at the arctic and antarctic polar vortex), so unresolved diffusion is higher than in CLaMS there. This is consistent with Hoppe et al (2014), who found in free-running simulations with the coupled model system EMAC-CLaMS, that transport barriers (polar vortex and tropical pipe) are stronger, if using the CLaMS tracer transport scheme compared to FFSL transport scheme. The stronger transport barrier in CLaMS can be also seen in Fig.…”
Section: Calculation Of Aging By Mixing On Resolved and Unresolved Scsupporting
confidence: 80%
“…A particular advantage of CLaMS Lagrangian transport is that the trajectory calculation is non-diffusive per se, and that the strength of diffusion induced by parametrized small-scale mixing may be controlled. For that reason, a critical Lyapunov exponent λ c has to be specified, which controls the relative distance between model grid points to be affected by mixing (for details see e.g., Hoppe et al, 2014). Table 1 gives an overview over all model simulations used for the present study.…”
Section: Model Description Of the Chemical Lagrangian Model Of The Stmentioning
confidence: 99%
“…This indicates a need for further improvements of the model dynamics, particularly the forcing by gravity waves (Brühl et al, 2007). Furthermore, in a more recent study by Hoppe et al (2014) it was shown that the standard flux-form semiLagrangian scheme used in EMAC may be too diffusive near the transport barriers and that the simulation results can be improved when a Lagrangian transport scheme is used instead.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted box-model simulations for which the impact of mixing is neglected; however mixing across the Antarctic vortex edge is frequently overestimated substantially in current chemistry climate models (Hoppe et al, 2014). For the box model, the development of temperature, potential temperature and solar zenith angle along a typical air parcel trajectory in Antarctic spring is shown in Fig.…”
Section: Maintenance Of Chlorine Activationmentioning
confidence: 99%